Uterovesical Fistula: A Rare Obstetrical Complication, An Emerging Challenge - Hassan, Nabila; Srichand, Pushpa; Talpur, Sabreena; Abbas, Sabreena (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the frequency of uterovesical fistula, its etiology, clinical presentation and management. METHODOLOGY: This retrospective study was carried out at department of Obstetrics and Gynecology from January 2007 to June 2018. Secondary data collected from hospital records of all patients who are diagnosed as a case of uterovesical fistula. Details regarding age, parity, duration, etiological factor, clinical presentation and management of uterovesical fistulae were recorded. Data analysis performed on SPSS version 20 and results were analyzed for mean, frequency and percentage. RESULTS: During the study, there were 545 patients registered with urogenital fistula. Among them 36 patients having uterovesical fistula were included in the study, giving a frequency of 6.6%. Mean age 26±8 while mean parity 3±2.4. Major etiological factor was caesarean section for obstructed labour (n=25, 69%) followed by repeat caesarean section. Major symptoms were urinary incontinence and cyclical menouria. Most of the patients (n=34, 94%) had surgical repair. All patients had complete cure. CONCLUSION: Uterovesical fistula is not an infrequent gynecological morbidity in our area with diagnostic challenge, however meticulous clinical evaluation keeping the possibility of this disease can give clue to the diagnosis. Though surgical approach can cure most of the cases, attention should be given towards preventive strategies such as provision of quality obstetric care with improvements of surgical skills.